Phosphatidylinositol 3-Phosphate Mediates the Establishment of Infectious Bursal Disease Virus Replication Complexes in Association with Early Endosomes - Gimenez, María Cecilia (J Virol, 2021)
Infectious bursal disease virus (IBDV) is the archetypal member of the family Birnaviridae and the etiological agent of Gumboro disease, a highly contagious immunosuppressive infection of concern to the global poultry sector for its adverse health effects in chicks. Unlike most double-stranded RNA (dsRNA) viruses, which enclose their genomes within specialized cores throughout their viral replication cycle, birnaviruses organize their bisegmented dsRNA genome in ribonucleoprotein (RNP) structures. Recently, we demonstrated that IBDV exploits endosomal membranes for replication. The establishment of IBDV replication machinery on the cytosolic leaflet of endosomal compartments is mediated by the viral protein VP3 and its intrinsic ability to target endosomes. In this study, we identified the early endosomal phosphatidylinositol 3-phosphate [PtdIns(3)P] as a key host factor of VP3 association with endosomal membranes and consequent establishment of IBDV replication complexes in early endosomes. Indeed, our data reveal a crucial role for PtdIns(3)P in IBDV replication. Overall, our findings provide new insights into the replicative strategy of birnaviruses and strongly suggest that it resembles those of positive-strand RNA (+ssRNA) viruses, which replicate in association with host membranes. Furthermore, our findings support the role of birnaviruses as evolutionary intermediaries between +ssRNA and dsRNA viruses and, importantly, demonstrate a novel role for PtdIns(3)P in the replication of a dsRNA virus. IMPORTANCE Infectious bursal disease virus (IBDV) infects chicks and is the causative agent of Gumboro disease. During IBDV outbreaks in recent decades, the emergence of very virulent variants and the lack of effective prevention/treatment strategies to fight this disease have had devastating consequences for the poultry industry. IBDV belongs to the peculiar family Birnaviridae. Unlike most dsRNA viruses, birnaviruses organize their genomes in ribonucleoprotein complexes and replicate in a core-independent manner. We recently demonstrated that IBDV exploits host cell endosomes as platforms for viral replication, a process that depends on the VP3 viral protein. In this study, we delved deeper into the molecular characterization of IBDV-endosome association and investigated the role of host cell phosphatidylinositide lipids in VP3 protein localization and IBDV infection. Together, our findings demonstrate that PtdIns(3)P serves as a scaffold for the association of VP3 to endosomes and reveal its essential role for IBDV replication.